Weak states and the commons: Fisheries and economic development in the Gaspé Peninsula circa 1830 - Vincent Geloso; Félix Foucher-Paquin (Journal of Government and Economics, 2023)
The inefficiencies of common property fisheries are well-known to economists. To avoid over-exploitation, they propose multiple forms of government solution such as taxes, quotas and the enforcement of property rights regimes designed to avoid over-harvesting. But can efficient arrangements also exist under statelessness, or in the presence of weak states? One such example is the Gaspé Peninsula (in the Canadian province of Quebec) during the first half of the nineteenth century. There, a single firm (the Charles Robin Company) came to dominate the market and was able to restrict entry effectively. In this paper, we explain that it was able to do so by reducing the prices on imported goods that it would give to local fishermen in exchange for a part of their catch. This had the effect of deterring fishermen from contracting with other merchants as well as deterring other merchants from entering the market. It also made the region richer than most regions of Canada at the time, contrary to what historians have depicted. We take this as an example of the ability to deal with commons problems in the presence of weak states.